2011
DOI: 10.1186/1752-153x-5-59
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for spectrophotometric determination of pregabalin in pure form and in capsules

Abstract: BackgroundPregabalin, a γ-amino-n-butyric acid derivative, is an antiepileptic drug not yet official in any pharmacopeia and development of analytical procedures for this drug in bulk/formulation forms is a necessity. We herein, report a new, simple, extraction free, cost effective, sensitive and reproducible spectrophotometric method for the determination of the pregabalin.ResultsPregabalin, as a primary amine was reacted with ninhydrin in phosphate buffer pH 7.4 to form blue violet colored chromogen which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 15 publications
(11 reference statements)
0
20
0
1
Order By: Relevance
“…Hosseinimehr et al (2010) reported a similar ninhydrin procedure for the estimation of baclofen, which is an analogue of GABA. The same protocol was applied by Bali and Gaur (2011) for the estimation of pregabalin, another analogue of GABA.…”
Section: Calorimetric Estimation Of Gabamentioning
confidence: 99%
“…Hosseinimehr et al (2010) reported a similar ninhydrin procedure for the estimation of baclofen, which is an analogue of GABA. The same protocol was applied by Bali and Gaur (2011) for the estimation of pregabalin, another analogue of GABA.…”
Section: Calorimetric Estimation Of Gabamentioning
confidence: 99%
“…The extraction method of the competition experiment was in accordance with that detailed in the Extraction experiments section. The amino acids were analyzed by ninhydrin‐colorimetry method . A curve reflecting the influences of the three typical amino acids on L‐Lys extraction was plotted with the molar ratios of the other amino acids (L‐Arg, L‐Asp, L‐Ala) to L‐Lys as abscissa and the extraction efficiency as vertical coordinate, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Several methods have been developed for the determination of the drug in pure and pharmaceutical preparations which are mostly based on chromatographic, spectrofluorimetric and spectrophotometric methods listed elsewhere (Bali and Gaur 2011). A detailed literature survey shows that few spectrophotometric methods have been developed for the determination of PGB in bulk and pharmaceutical preparation.…”
Section: Pregabalinmentioning
confidence: 99%